Mudanças e conflitos nos paradigmas missionários católicos no colonialismo tardio em Moçambique - Almeida, João Miguel (Lusitania sacra, 2025)
The Catholic missionary paradigm manifested in the agreement between the Portuguese state and the Holy See in the 1940 Concordat and Missionary Agreement, attributes to the Catholic Church an ‘imperial utility’ and a ‘civilising’ sense, associated with Portuguese nationalism. After the Second World War, this vision gave way or came into conflict with new missionary paradigms based on the ideas of ‘development’ or ‘liberation’. During the period of late colonialism (1961-1974), the conflicts between the different missionary paradigms were linked to the various political and ecclesial conflicts.